The relationship between an athlete`s maximal aerobic speed determined in a laboratory and their final speed reached during a field test (UNCa Test) - Cappa, D. F.; Garcia, G. C.; Secchi, J. D.; Maddigan, M. E. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: The main purpose of this study was to apply a field test to predict the maximal aerobic speed (MAS) of an athlete using the same protocol done in a laboratory.